Pengaruh Pola Asuh Ibu Terhadap Perkembangan Kepribadian Tokoh Hikaru Narumi dan Hiro Narumi dalam Manga Piece Karya Ashihara Hinako - Prischa Sisilia, Vitaloka; Andry Anita Dewi, Ni Made; Damayanti, Silvia (Humanis, 2016)
The title of this study is “The Influence of Parenting Mother Against The Personality Development of Character Hikaru Narumi and Hiro Narumi in Manga entitled Piece by Ashihara Hinako”. The aims of this study to analyze and explain the influence of parenting mother against the personality development of character Hikaru Narumi and Hiro Narumi in manga entitled Piece by Ashihara Hinako. The theories that are used for analyzing are literary psychology by Roekhan (2008), parenting parents style by Hurlock (2011), personality development by Erickson (2011), and semiotics by Danesi (2010). The results of this study showed that Risako Narumi used two parenting style to Hikaru Narumi and Hiro Narumi pervaded authoritarian parenting and permissive parenting. From authoritarian parenting that used by Risako resulted her sons have personally closed (introvert), selfish and indifferent. While permissive parenting that used by Risako resulted her sons be unable to determine a good or bad choice and not consistent.